2005
DOI: 10.1248/bpb.28.1672
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Human Intestinal Bacterium That Transforms Mangiferin to Norathyriol and Inducibility of the Enzyme That Cleaves a C-Glucosyl Bond

Abstract: C-Glucosides, which are widely distributed among plants, are more resistant towards acid, alkaline and enzyme hydrolysis than O-glucosides. Even prolonged exposure to acid does not cleave the glucosyl bond of C-glucosides, in which glucose is attached by a carbon-carbon bond to the aglycone, to give the aglycone. 1) However, intestinal bacteria from human feces can cleave C-glucosyl bonds in various C-glucosides such as mangiferin, abrusin 2Љ-O-b-D-apioside, aloeresin A, aloesin, barbaloin, bergenin, homoorien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 30 publications
3
57
0
2
Order By: Relevance
“…In addition, Sanugul et al (2005) and Braune and Blaut (2011) have isolated human intestinal bacteria, named Bacteroides sp. MANG and CG19-1, respectively, both of which could transform mangiferin into its aglycone norathyriol in vitro.…”
Section: Liu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Sanugul et al (2005) and Braune and Blaut (2011) have isolated human intestinal bacteria, named Bacteroides sp. MANG and CG19-1, respectively, both of which could transform mangiferin into its aglycone norathyriol in vitro.…”
Section: Liu Et Almentioning
confidence: 99%
“…Considering the antidiabetic effects of mangiferin, it is important to investigate its pharmacokinetics and metabolism in diabetic animals. Previous in vitro studies (Sanugul et al, 2005;Braune and Blaut, 2011;Liu et al, 2011) indicated that mangiferin might be metabolized into norathyriol by the intestinal flora. Thus, it is conceivable that the role of intestinal flora in the metabolism of mangiferin is critical and its alterations may affect the metabolic and pharmacokinetic behavior of mangiferin in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] These naturally occurring compounds and their synthetic analogs have been reported to exhibit multiple important pharmacological properties, such as anti-oxidant, anti-inflammatory, anti-malarial and anti-cancer activity, etc. [4][5][6][7][8][9] As shown in Fig. 1a, xanthones having three linear fused aromatic rings may be viewed as flavone derivatives in which the phenyl group is fused with the two aromatic rings.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9] As shown in Fig. 1a, xanthones having three linear fused aromatic rings may be viewed as flavone derivatives in which the phenyl group is fused with the two aromatic rings.…”
mentioning
confidence: 99%
“…Quantitative Analysis of Mangiferin and Its Product, Norathyriol, by HPLC 22) The conditions used for reversed phase HPLC (Shimadzu Co., Japan) were as follows: recorder, C-R6A Chromatopac; pump, LC-6A; system controller, SCL-6B; monitor, SPD-6A; injector, SIL-9A; column, YMC-Pack ODS-AP AP-302 (YMC Co., Kyoto, Japan); flow rate, 1 ml/min; detection, 260 nm; solvent system, 10-40% acetonitrile linear gradient in 0.1% trifluoroacetic acid.…”
mentioning
confidence: 99%